"The Opening of the Mouth"—A New Perspective for an Ancient Egyptian Mummification Procedure. Issue 6 (June 2015) - Seiler, Roger; Rühli, Frank
ABSTRACT "The opening of the mouth ritual" (OMR) is a central and well‐documented component of the Ancient Egyptian mortuary ceremony. In the scientific literature, we find various references that indicate that parts of this ritual correspond to physical opening of the deceased's mouth during its mummification. We denote this physical treatment of the dead the "opening of the mouth procedure, " to underline the distinction against the "opening of the mouth ritual, " which is performed ceremonially later on the mummy or even the statue. The mummifying procedure itself however is known only from rare pictorial representations and the later summary descriptions of Greek authors. Nevertheless, recently some authors tried, on the basis of paleopathological findings, to demonstrate that the mouth of the deceased had to be opened physically before mummifying. Careful examination of the mummies of the Swiss Mummy Project and other cases reported in the literature showed frequent dental pathologies including fractured and totally luxated teeth, which were up to now not sufficiently taken into consideration. The detailed report of the preliminary procedures of mummifying the Apis bull—as appropriate detailed descriptions for humans are missing—gives us insight into the treatment of the oral cavity. Our results, when combined with the available historical literature, indicate that the OMR can be regarded as a ritualized counterpart of a real "opening of mouth procedure" during mummification. Anat Rec, 298:1208–1216, 2015. © 2015 Wiley Periodicals, Inc..